Design and Simulation of E-Vehicle Charging Substations with Load Flow and Performance Analysis (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The rapid adoption of electric vehicles (EVs) has created a pressing need for efficient, reliable, and scalable charging infrastructure integrated with existing power distribution networks. This paper presents the design and simulation of electric vehicle charging substations with a focus on load flow and performance analysis. A detailed substation model is developed considering typical EV charging loads, transformer ratings, feeder configurations, and protection constraints. Load flow analysis is carried out to evaluate key performance parameters such as voltage profile, power losses, loading conditions, and system stability under different charging scenarios. Simulation results demonstrate the impact of high EV penetration on distribution networks and highlight critical operational challenges, including voltage deviations and increased losses. The proposed design framework aids in optimizing substation capacity planning and operational efficiency, ensuring reliable power delivery to EV charging stations. The findings provide valuable insights for utilities, planners, and researchers involved in the development of sustainable EV charging infrastructure.